Clinical characteristics of a new coronavirus infection (COVID-19) in children hospitalized in a hospital in Karaganda - D. G. Bolatova; M. K. Kayrgel'dinova; M. Ye. Kazhybay; A. S. Myrzakulova; S. A. Turlybekova; M. A. Sin; D. Ye. Zhupenova; P. A. Omirzakova (Детские инфекции (Москва))
The aim of the study was to study the features of the course of a new coronavirus infection COVID-19 in hospitalized children.Materials and methods. Clinical manifestations of COVID-19 were studied in 859 children aged 3 months to 16 years old, hospitalized in the children's hospital of Karaganda, Kazakhstan, in the first 6 months of 2021. In all patients, the diagnosis of COVID-19 was confirmed by the detection of SARS-CoV-2 RNA by PCR in nasopharyngeal swabs.Results. In 60% of cases, children aged 7 years and older were ill. More than half of the children (67.6%) had a mild form of the new coronavirus infection COVID-19, and only a third of the patients had a moderate form (31.2%) and 1.2% had a severe form. One child had a multi-inflammatory syndrome (Kawasaki-like). Half of the children had subfebrile or febrile fever (51.1%) and cough (51.2%), as well as signs of intoxication (35.9%), diarrhea (2.4%). In a third of children, the diseaseproceeded with damage to the lower respiratory tract, with bronchitis and  pneumonia (7.8 and 20.3% of cases, respectively). In the general blood test,  leukopenia (33.6%), lymphocytosis (45%) were noted.Conclusion. In the first half of 2021, in hospitalized children in Karaganda, Kazakhstan, the new coronavirus infection COVID-19 proceeded favorably in the vast majority of cases.